Аpplication of precedent technology to support decision-making to ensure the efficiency of complex technical systems - Vychuzhanin, A.V. (My University, 2024)
Such systems are hierarchical structures with non-trivial internal structures, multiple functional subsystems, components, elements and complex connections between them, which are in various states of failure. The operation of СTS is subject to uncertainties that are difficult or impossible to fully describe, understand or predict. One of the main causes of man-made accidents associated with the operation of СTS used in transport, aviation, energy, etc. remains the failure of their subsystems, components, and elements [3]. With increasing requirements for the safety of expensive СTS, the requirements for their efficiency, which depend on the time and resource during operation of the systems, are simultaneously increasing.
Keywords: прецендентні технології; прийняття рішень; комплекс технічних систем; precedent technologies; decision-making; complex of technical systems